Bats of the Wind Cave Nature Reserve, Sarawak, Malaysian Borneo - Mohd Ridwan, A.R; Tingga, Roberta Chaya T.; Mohd Isham, A.; H., Noor Haliza; M.T, Abdullah (Chulalongkorn University, 2011)
A survey of the chiropteran species at the Wind Cave Nature Reserve (WCNR) in the Bau limestone areas (BLA), Sarawak, was conducted from the 10th to 20th January 2008 and the 10th to 20th April 2009. A total of 297 and 367 (net 646) individuals, representing 14 and 11 (net 17) species from four families were captured in 2008 and 2009, respectively, from an effort of 143 each (net 286) sampling nights. This represents eight new recordings for the WCNR and approximately 85%, 45.9% and 17.7% of the total species recorded in the WCNR, BLA and Borneo, respectively. Over both years the most commonly captured species was by far Penthetor lucasi followed by Hipposiderous cervinus, which were comprised of 63% and 22% of the total (2008 + 2009) captures, respectively. Four and eight species were recorded as the new locality records for Wind Cave (WC) and WCNR, respectively, with Rhinolopus arcuatus*, H. larvatus*, H. coxi*, H. ridleyi, H. galeritus*, Kerivoula pellucida, Tylonycteris robustula and T. pachypus being new records for WCNR and those marked with an asterix (*) being new records for WC. This documentation is of importance for forest conservation and management in future.